Use the external radiotherapy StarTrack detector to study the electron beam profile - Safa Sami Hassan, (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the electron beam dose verification, and to investigate the dependability and stability of the Startrack two-dimensional array. Method: The is a cross-secional study was conducted from January to April 2021 at the Baghdad Centre for Radiotherapy and Nuclear Medicine, Baghdad Medical City, Baghdad, Iraq. quality assurance measurements were made using a StarTrack two-dimensional detector on an electron beam with an energy of 12MeV at 1.5cm depth for field sizes 6cm×6cm and 14cm×14cm. The detector was positioned 100cm from the source to the surface of the linear accelerator infinity. Testing was done using the International Electrotechnical Commissioning protocol. Results: There was a significant difference between field sizes 6cmx6cm and 14cmx14cm (-4.97±0.83, -2.01±0.68, respectively) (p<0.05). The beam profile measurements of penumbra, flatness and symmetry were within limits ±2 cm, and ±2 cm, 2%, respectively. The percentage of output dose curve against distance showed instability in crossline for 6cm x 6cm and 14cm x 14cm field size. Conclusion: The output dose was found to be above the tolerance level, and should be corrected before patient treatment for 12MeV energy electron beam therapy. Key Words: Electrons, Nuclear Medicine, Radiotherapy,